Aerobic Composting of Municipal waste (Journal of Hama University, 2019)
An aerobic digestion for solid waste samples which had been mixed randomly to represent the normal (real) case, and for samples prepared to have Carbon to Nitrogen C:N equal (1-30) as an ideal case. The result of this process was a dry matter has 1:3 the original weight of the used solid waste in the digestion and this product was called compost. The duration of digestion for ideal case was (23) days in summer and (27) days in winter, while for normal case it was (30,33) in summer and winter respectively. In this research several factors effecting on the digestion such as (temperature of air and mix, pH variation ,water content and volume reducing of solid mixture were studied). we concluded that the effect of air temperature variation was mild on digestion, and the water content was in the ideal range of the process,. The solid waste volume decreased in the end of digestion process for ideal case to (37,40.5)%, while decreased to (39,41)% for real case in the summer and winter respectively. The produced compost in both case was shown free from pathogenic microorganism and rich in nutrients (N, P, K) and their concentrations approach to commercial compost as well as their economic value. It has been found that the heavy metals concentrations in the resultant compost were in the standard limits.